Iranian Herbal Medicines Against Hydatid Cyst Protoscoleces: A Systematic Review - Salimikia, Iraj; Hakami, Marzieh; Shahmoradi, Mohammad K. (Infectious Disorders - Drug Targets, 2021)
Background: In recent years, more attention has been focused in the practice of both crude extract of medicinal plants, and the screening plant-derived compounds as substitute scolicidal agents during hydatid cyst surgery. The present study was designed to review the protoscolicidal effects of some Iranian herbal medicines against hydatid cyst protoscoleces. Methods: English databases, including PubMed, Google Scholar, Web of Science, EBSCO, Science Direct, and Scopus were searched for publications worldwide related to protoscolicidal effects of Iranian herbal medicines without date limitation so that identify all published articles (in vitro, in vivo, clinical and case-control) have studied. Keywords included “Protoscolicidal”, “Scolicidal”, “Herbal medicines”, “Extract”, “Essential oil”, “Plant”, “In vitro”, and “Iran”. Moreover, the language of data collection was limited to English. Results: In total, 40 papers up to 2020 were included in the present systematic review. The most studies were conducted on protoscolicidal activity of methanolic extracts (17 studies) followed by essential oils (15 studies), and aqueous extract (3 studies). The most commonly used part of herbs were leaves (21 herbs), seeds (8 herbs), and fruit (6 herbs), respectively. Moreover, the most prevalent herbal family was Lamiaceae (6 studies), followed by Apiaceae (5 studies) and Liliaceae (5 studies). Conclusion: Considering the high efficacy of Iranian herbal medicines against hydatid cyst protoscoleces, it can be concluded that Iranian herbal medicines have ability to consider as new alternative protoscolicidal agents during hydatid cyst surgery; however, more clinical studies are required to discover the precise protoscolicida activity of Iranian medicines in animal and human subjects.
Keywords: Cystic echinococcosis